Human Resource Management (HRM) Practices Across Different Cultures: An Evidence-Based Study In United States And China - Dendy Maulana Yusuf; Grace Tofer Claudius Close One Prinsen Wahyudiono; Zanuar Fikri Maulana (Lavish Opulent Education, 2024)
In this study, explain about the differences in Human Resource Management (HRM) practices between the United States and China. The focus is on recruitment selection, development, development, occupational safety and health, industrial relations and occupational assessment. The methodology used is a literature study with a descriptive - qualitative approach. This research utilizes a variety of written sources, including journal articles, websites, and related documents, to describe cross-cultural HR practices in both countries. Data processing involves the selection of information and comparison between practices in both countries. This research provides a more indepth and broad analysis of human resource management (HRM) practices in the United States and China, with emphasis on six key aspects: recruitment, selection, development, occupational safety and health, industrial relations, and job assessment. The study reveals how different cultural values and business systems in these two countries affect the implementation and effectiveness of HRM practices.